(untitled) (Bangladesh Journal of Botany, 2026)
The experiment was carried out at the experimental farm, Department of Vegetable Science, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan, HP, India during 2022 and 2023 to study the mean performance, heterotic expression for yield and quality traits in chilli. The experimental material comprised of eight diverse chilli genotypes, crossed in half-diallel mating design during 2022 to obtain 28 cross combinations. The 28 F1 crosses along with 8 parental genotypes and 1 check DKC-8 were evaluated in RCBD during 2023. Surajmukhi, Punjab Guchhedar and Arka Lohit among parents and cross combinations viz. Surajmukhi × Punjab Tej, Surajmukhi × Arka Lohit, Kashmir long-1 × Surajmukhi and Punjab Guchhedar × Arka Lohit performed best for dry fruit yield per plant. The top three cross combinations for dry fruit yield per plant showing significant positive heterosis over better parent were Punjab Tej × Pusa Jwala, Punjab Guchhedar × Arka Lohit and Kashmir long -1 × Punjab Tej. Bangladesh J. Bot. 55(1): 153-159, 2026 (March)